Diseño y desarrollo de una plataforma digital de apoyo a la docencia y a la investigación en Archivos Electrónicos: un portal temático Thematic Web portals, Web portals, Portals, Electronic archives, Electronic records - Antonio Ángel Ruiz Rodríguez y David Gómez Domínguez (Information Research: An International Electronic Journal)
The present contribution is aimed at explaining in detail a thematic Web portal specialized in digital documents and their impact on the information society from the archives and records management perspective. It has been produced by the Faculty of Library Science and Documentation of the University of Granada. This web portal has been developed as the basis of a digital platform for practical exercises in subjects linked to this area which form part of a Masters degree in Documentation. Thus, the development of practice will be enhanced and supported with a wide range of relevant information resources on this subject. As the portal will support both teaching and research, it contributes to the principal objectives of the university.